The Influence of The Two Stay Two Stray Learning Model on The Responsible Character of Fourth-Grade Elementary School Students in Science Learning - Rukoyah, Siti; Yuliyanto, Aan; Amanaturrakhmah, Isna; Nurjanah, Nunung; Wulandari, Tita Dwi; Muslim (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The character of responsibility is an essential behavior for someone, including elementary school students, so they have this excellent character at school and outside school. This study aims to understand the influence of the two stay two stray learning models on the responsible character of fourth-grade elementary school students in science learning. This literature study was developed through various sources such as books, journals, and other literature related to the characters and learning models studied. In the two-stay-two-stray learning model, students must be responsible and active in every learning activity. This learning method can increase student communication in socializing and make the class atmosphere more lively. Apart from Increasing students' responsibility in carrying out their assignments so that their responsible character is also embedded in their daily lives, students can practice making assignment reports. In carrying out this model, the tributes different tasks to each group, where students must carry out the tasks well and correctly according to the teacher's order.